Structuring an advertising business in Vietnam (an example of FPT media - the corporation for financing and promoting technology) : Luận văn ThS. Kinh doanh và quản lý: 60.34.05 - Pham, Vu Duc (Đại học Quốc gia Hà Nội, 2017)
100 p. + CD-ROM